ADAKAH PENGARUH FREE FLOAT TERHADAP PELAKU PASAR SAHAM DI INDONESIA? - PUTRI MUTIRA (Jurnal Bisnis dan Akuntansi, 2019)
Indonesian Stock Exchange has released free float adjustment index on November 2018 and composite index declined about 3,2%. Free Float will be an additional reference for the exchange in compiling an index which previously used market capitalization and total transaction value. This study examines the average daily price changes of LQ45 stocks within 60 days before and after the announcement. The daily closing price changes are calculated as a percentage increase or decrease of stock prices according to the previous day, then, the average value is calculated for all the trading days. There are differences in the average stock price changes 60 days before and after the announcement date. After dropped, the price rebound and make a new higher high price two days after the announcement. Bank BCA, Bank Mandiri, Bank BRI, Bank BNI, Astra International and Telkom are companies which increase the weight of the free float meanwhile Unilever and H.M Sampoerna were the opposite.